Mathematical modeling reveals a critical role for cyclin D1 dynamics in phenotype switching during glioma differentiation. Issue 18 (17th July 2015) - Sun, Xiaoqiang; Zheng, Xiaoke; Zhang, Jiajun; Zhou, Tianshou; Yan, Guangmei; Zhu, Wenbo
Abstract : Glioma differentiation therapy is a novel modality to increase anti‐glioma effects using specific drugs to induce glioma cell differentiation to glia‐like cells. However, the molecular mechanisms underlying glioma differentiation remain poorly understood. In this study, we built an experiment‐integrated mathematical model for glioma differentiation signaling pathways. Our modeling and experimental analysis revealed that a "one‐way‐switch" bifurcation of cyclin D1 dynamics was critical for controlling the phenotypic transition of glioma cells. We also quantitatively evaluated drug combinations toward a synergistic therapeutic effect. These results provide insights into the molecular mechanisms underlying glioma differentiation and implications for the design of novel therapeutic targets in anti‐cancer therapy. Abstract : An experiment‐integrated mathematical model of signaling pathways involved in glioma differentiation was developed. Model analysis revealed that bifurcation dynamics of cyclin D1 control the glioma cell phenotype transition from proliferation to differentiation. Experimental validation confirmed the critical role of cyclin D1 in glioma phenotype switching.